The Effect of Market Timing Ability, Stock Selection Skill and Risk Levels on Sharia Stock Mutual Funds Performance with The Inflation Level as A Variable of Conditional and Unconditional Models in Period 2015-2017 - Dona Merti; Emrinaldi Nur; Nasrizal Nasrizal (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
The research aims to examine The Influence of market timing, stock selection skill and level risk to performance of equity funds with inflation as intervening variable. Object of thisresearch are secondary data is data that NAB is a sample of 2015-2017 in the form of daily data which are sixty data of equity funds. That data are analyzed by multiple regression method and SPSS program version 21. The variables were examined are influence of market timing,stock selection skill and level risk to performance of equity funds with inflation as intervening variable. The results of this research showed that market timing ability, stock selection skill and level riskhave effect to inflationwith significance, market timing, stock selection skill and level risk also have effect to performance of equity funds with significance, but with inflation as intervening variable only market timinghas an effect to performance of equity funds neither for stock selection skill to performance of equity funds. The results of this research also showed that the significance is under 0,05, which means the effect is well-strong. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain  dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study as fund size and level return.